Investigation of bacterial pathogens in milk from mastitic dairy cattle by matrix-assisted laser desorption ionization-time of flight mass spectrometry - Ozbey, Gokben; Otlu, Baris; Yakupogullari, Yusuf; Celik, Betul; Tanriverdi, Elif Seren; Kelestemur, Neslihan; Sproston, Emma (Chulalongkorn Univ, 2022)
The scope of the present study was to assess the use of Matrix-Assisted Laser Desorption/Ionization-Time of Flight (MALDI-TOF) Mass Spectrometry (MS) as a quick technique for the identification of bacterial species in mastitis. In this study, milk samples from each udder quarter from a total of 250 dairy cattle were aseptically collected and tested. The samples were grouped into California Mastitis Test (CMT) positive, CMT negative and clinical mastitis. The samples were streaked on blood agar and the bacterial isolates were analysed using MALDI-TOF MS. Using MALDI-TOF MS, certain species such as Staphylococcus chromogenes (44/188, 23.4%), Aerococcus viridans (40/188, 21.3%) and Staphylococcus haemolyticus (19/188, 10.1%) were identified at a higher proportion in milk samples from cattle that were CMT positive. Moreover, the most common bacteria isolated from CMT negative milk samples were A. viridans (56/161, 34.8%), S. haemolyticus (24/161, 14.9%) and S. chromogenes (17/161, 10.6%). Only one isolate of S. chromogenes (1/4, 25%), A. viridans (1/4, 25%), S. haemolyticus (1/4, 25%) and Enterococcus faecium (1/4, 25%) was detected from milk samples with clinical mastitis using MALDI-TOF MS. There was a concurrence between the MALDI-TOF and biochemical bacterial identification method in 325 of 353 samples (92.06%). This study concludes that MALDI-TOF can be applied for quick determination of bacterial isolates once the bacterial colony has been isolated in milk samples.
Keywords: Cattle; California Mastitis Test; MALDI-TOF; milk samples